Abundance and Distribution of the Invasive Ant, Solenopsis invicta (Hymenoptera: Formicidae), in Cypress Savannas of North Carolina. (1st November 2014) - Kelly, L; Sellers, J
Abstract: The ecological effects of invasive ants on ecosystems will depend largely on ant abundance. Cypress savannas of the southeastern United States have high conservation worth, supporting diverse and rare assemblages of species. Distance sampling was used to determine the abundance and distribution of colonies of the invasive ant, Solenopsis invicta Buren, in cypress savannas of two Carolina bays. Colonies were distributed throughout the savannas, save for areas of dense tree or shrub cover. Colony densities were much less than those reported for disturbed habitats and were similar between bays. Free-standing mounds were more common in the historically less flooded bay, and they had significantly greater volume and colony biomass as compared with these mounds in the other bay. Unlike previous studies, reporting only monogyne colonies for intact habitats of the southeast, both monogyne and polygyne colonies were present in the cypress savannas; <60% of the colonies were monogyne. Cypress savannas join a growing list of habitats, having wet sandy or loamy soils and little canopy, that have become invaded by S. invicta in the absence of anthropogenic soil disturbances. Cypress savannas resemble invaded longleaf pine savannas in vegetation physiognomy, history of fire, and dense herbaceous ground cover. While fires are critical for biodiversity, the resulting dense herbaceous ground cover may favor S. invicta . As generalist consumers and likely the most abundant ant species in these habitats, S. invicta could have important direct and indirect effects on the native communities.